2020
DOI: 10.1177/0023677220911680
|View full text |Cite|
|
Sign up to set email alerts
|

Severity assessment using three common behavioral or locomotor tests after laparotomy in rats: a pilot study

Abstract: The aim of this pilot study was to evaluate whether behavioral or locomotor tests (Open Field (OF), rotarod (RR), and CatWalk (CW)) can help assess the severity of laparotomy in rats. The new EU Directive (2010/63/EU) mandates severity assessment in experiments involving animals. However, validated and objective methods are needed to relate trial-specific monitoring results to the degree of distress caused to individual animals. Therefore, we focused on non-invasive or minimally invasive, simple, and convenie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…In a previous study, we reported laparotomy-induced changes in moving activities of rats in the OF test [ 6 ]. The results demonstrated that animals show less activity with increasing distress or pain.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In a previous study, we reported laparotomy-induced changes in moving activities of rats in the OF test [ 6 ]. The results demonstrated that animals show less activity with increasing distress or pain.…”
Section: Discussionmentioning
confidence: 99%
“…On D-15 (surgery I), a telemetric transmitter (hereafter referred to as transmitter implantation, TI; Data Sciences International, Minnesota, USA; HD-S11) was surgically implanted subcutaneously in the left flank in 12 animals of each 7-day survival group. All animals in the Sham group were implanted with a dummy device, as these animals were part of a pilot study [ 6 ] performed before studying PH. Transmitter implantation was followed by a 12-day recovery phase with no further intervention.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…If no corresponding intervention was found in the catalogs, this position is white. 1 Pogatzki and Raja ( 42 ); 2 Buvanendran et al ( 49 ); 3 Duarte et al ( 50 ); 4 Brennan et al ( 43 ); 5 Kendall et al ( 51 ); 6 Flatters ( 30 ); 7 Ho Kim and Mo Chung ( 52 ); 8 Bennett and Xie ( 53 ); 9 Decosterd and Woolf ( 54 ); 10 Buvanendran et al ( 46 ); 11 Jimenez-Andrade et al ( 55 ); 12 Lu et al ( 56 ); 13 Ren et al ( 57 ); 14 Awsare et al ( 58 ); 15 Zieglowski et al ( 59 ); 16 Llovera et al ( 60 ); 17 Kyweriga et al ( 61 ).…”
Section: Exemplary Application Of the Wwhow Conceptmentioning
confidence: 99%